Benzoxazines with enhanced thermal stability from phenolated organosolv lignin. Issue 109 (11th November 2016) - Abarro, Ghizelle Jane; Podschun, Jacob; Diaz, Leslie Joy; Ohashi, Seishi; Saake, Bodo; Lehnen, Ralph; Ishida, Hatsuo
Abstract : Phenolated lignin was modified with propargyl amine and aniline to benzoxazines, which exhibit high thermal stability and were classified as self-extinguishing. Abstract : Lignin-based benzoxazines are synthesized for the first time using organosolv lignin as the phenolic component and aniline or propargyl amine as the amine component through the Mannich condensation reaction. Acid-catalyzed phenolation of organosolv lignin is performed to increase the phenolic structure with the open ortho -position, which is a requirement for an oxazine ring formation. Two model compounds using o -cresol and p -cresol as the phenolic component and propargylamine as the amine component are also synthesized for comparison. The successful syntheses are verified by Fourier transform infrared spectroscopy (FT-IR); proton, carbon and phosphorus nuclear magnetic resonance spectroscopy ( 1 H, 13 C and 31 P NMR); and elemental analysis. Further structural characterization of the precursor resins is performed using heteronuclear single quantum coherence (HSQC) NMR technique. The polymerization process is followed by both differential scanning calorimetry (DSC) and in situ isothermal FT-IR technique. The polymerization of the lignin-based benzoxazines proceeds faster than ordinary benzoxazine monomers due to the catalytic effect of the residual phenolic moieties in the lignin units. The majority of polymerization process takes place in less than 15 min at 180 °C for both lignin-based benzoxazines studied. The thermal stability of the polymers under study is evaluated by thermogravimetric analysis (TGA). The char yields of the polybenzoxazines derived from the lignin-based benzoxazines are close to 50%, which lead to LOI values considered self-extinguishing.